2010
DOI: 10.1159/000287588
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in Labor and Delivery

Abstract: Ultrasound may play an important role in the management of labor and delivery. Induction of labor is a common obstetric intervention, performed in about 20% of pregnancies. Pre-induction cervical length, measured by transvaginal sonography, has been shown to have a significant association with the induction-to-delivery interval and the risk for cesarean section. In the management of labor there is extensive evidence that digital pelvic examination does not provide accurate assessment of the position and descen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
49
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 45 publications
0
49
0
2
Order By: Relevance
“…However, there is much evidence that palpation performed during childbirth is inaccurate and does not allow for precise deter-mining the progression of head in the birth canal and that it is prone to a high number of errors in the evaluation of position and lie of the presenting part in both the first and second stage of labor [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is much evidence that palpation performed during childbirth is inaccurate and does not allow for precise deter-mining the progression of head in the birth canal and that it is prone to a high number of errors in the evaluation of position and lie of the presenting part in both the first and second stage of labor [4].…”
Section: Introductionmentioning
confidence: 99%
“…Molina and Nicholaides write that intrapartum ultrasound may help evaluate whether pregnancy will end in a vaginal delivery and Ghi et al reports that the assessment of head progression in the birth canal during the second stage of labor may play a role in predicting the manner of delivery [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…2 Akmal et al reported that digital VE failed to determine the fetal head position in 34% of laboring women, and incorrectly determined head position in 51% of patients in whom the position could be defined. 3,4 Digital VE are shown to be associated with infection ascending to the fetus, chorioamnionitis, endometritis and shortened time interval to delivery in preterm labor. 5,6 Digital VE have also been shown to frequently be experienced as painful and embarrassing to the women being examined.…”
Section: Introductionmentioning
confidence: 99%
“…HD. Finally, this parameter is quantified by measuring the direction angle (DA) between the IL and the HD 11,14 . In some studies 4,10 , HD is classified in this final step in relation to the SPla: 'head up' (when it points ventrally at an angle of > 30…”
mentioning
confidence: 99%